2017
DOI: 10.3342/kjorl-hns.2017.00430
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Body of External Auditory Canal: Review of 170 Cases

Abstract: Foreign bodies (FB) in the external auditory canal are relative medical emergency. The objective of this study was to describe the types of FB and their complications and to highlight on new FB not seen before which was the bluetooth devices that were used for cheating during high school examination in Al-Fallujah city. This was a two-year hospital-based descriptive study performed in the Department of Ear, Nose and Throat (ENT), Al-Fallujah General Hospital, from June 2011 to May 2013; during this period, 224… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 20 publications
4
10
2
Order By: Relevance
“…Patients with a foreign body in the ears presented with symptoms of ear pain and stuffiness. Contrary to previous studies, which found insects and cotton swabs as the most common foreign bodies, we found toys (e.g., buttons, clay, pencils, crayons, stickers, marbles, paper, and magnets) to be the most common foreign bodies, while insects were the fourth most common foreign bodies [ 2 , 9 ].…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Patients with a foreign body in the ears presented with symptoms of ear pain and stuffiness. Contrary to previous studies, which found insects and cotton swabs as the most common foreign bodies, we found toys (e.g., buttons, clay, pencils, crayons, stickers, marbles, paper, and magnets) to be the most common foreign bodies, while insects were the fourth most common foreign bodies [ 2 , 9 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies have demonstrated a higher frequency in children under 5 years of age, in agreement with our findings [ 3 , 9 , 10 ]. A previous study reported that the ear was the most common location, but we found that the throat was the most common location across all age groups [ 2 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…12 Our study also showed that the types of FB varied according to the age of patients, as have others. 12,13 Children younger than 10 years tend to have FBs related to toys such as airgun pellets and marbles. 14 With age, the proportion of toys decreased while cotton balls, insects, and earring materials increased.…”
Section: Discussionmentioning
confidence: 99%